Analisis Faktor-Faktor Yang Berperan Terhadap Kolaborasi Antara Dokter Dan Perawat Di Rumah Sakit Permata Medika Semarang - Irena Intania; Untung Sujianto; Sutopo Patria Jati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
Poor collaboration can affect the quality of service to patients, thus affecting the recovery of patients. For the profession, collaboration can affect the relationship and the job satisfaction of both doctors and nurses. Poor collaboration between doctors and nurses in hospital management can can influence a decrease number of Bed Occupation Rate and an increase in length of stay so that it can have an impact on patient satisfaction.This study used a quantitative design and descriptive analytic with qualitative approach through observation, review of documents, in-depth interviews with informants who already selected and determined using cross sectional approached. The sample in this study were all general practitioners and all nurses who work in Permata Medika Hospital until December 2015, ie 15 doctors and 15 nurses.The results show that the control of power is still difficult due to a balanced relationship between the two professions and poor communication. The scope of practice between doctors and nurses has established good collaboration. The shared interests of the two professions do not pay attention and see the procedure of service. At the collaborative goals of doctors and nurses there is overlapping responsibility for reasons of rushed work without regard to the Standard Operating Procedure (SOP) and job description.The Recommendations for management are need to be carried out definite career path for nurses, increase the knowledge and enhance the collaboration both nurses and doctors, increase the collaboration between nurses and doctors, follow up the results of service audits need to be coordinated and controlled